The TSST triggers self-reported stress and biological stress and frustrates basic psychological needs: general and specific buffering effects of physical activity and social support - Schüler, Julia; Rindelhardt, Simona; Ditzen, Beate (Stress, 2025)
Situations characterized by uncontrollability and critical social evaluation frustrate basic psychological needs, as outlined in Self-Determination Theory (SDT). Uncontrollability and social evaluation are central elements of the Trier Social Stress Test (TSST), leading to the hypothesis that the TSST, in addition to increasing self-reported stress and cortisol responses, also frustrates the needs for autonomy, competence, and social relatedness. Participants (N = 195) reported elevated stress and reduced need satisfaction, and increased cortisol responses during the TSST. The roles of assessed physical activity and experimentally-induced social support were also examined. Indeed, in time-sensitive and specific manner, the TSST frustrated basic psychological needs. Social support however mitigated frustration of social relatedness. Physical activity buffered against self-reported stress, the frustration of competence and the cortisol response. Further research is recommended to explore more differentiated interventions that can counteract the negative effects of psychosocial stressors.
Gesehen am 21.10.2025